Synthesis of deuterium‐labeled 2‐quinoxalinecarboxylic acid and 3‐methylquinoxaline‐2‐carboxylic acid from deuterium aniline. (2nd September 2018) - Chen, Wulian; Zhao, Chaomin; Deng, Xiaojun
Abstract : An efficient and simple synthetic route of deuterium‐labeled 2‐quinoxalinecarboxylic acid‐ d 4 (QCA‐ d 4 ) and 3‐methylquinoxaline‐2‐carboxylic acid‐ d 4 (MQCA‐ d 4 ) is presented with 99.9% and 99.6% isotopic enrichment using aniline‐ d 5 as labeled starting material. Their chemical structures were confirmed by 1 H NMR, and their isotopic abundance was determined by mass spectrometry analysis. Abstract : An efficient and simple synthetic route of deuterium‐labelled 2‐quinoxalinecarboxylic acid‐ d 4 (QCA‐ d 4 ) and 3‐methylquinoxaline‐2‐carboxylic acid‐ d 4 (MQCA‐ d 4 ) is presented. Their chemical structures were confirmed by 1 H NMR, and their isotopic abundance was determined by mass spectrometry analysis.